, ; Career expectations of students and doctoral researchers in agricultural universities in Kazakhstan - Gulnar Bekenova (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
, () , . 2009 « » . . - , , , . , , . . , , . , , - . , , , , , , - , , . – – In Kazakhstan, the state allocates educational grants for agricultural specialties annually, but agriculture lacks qualified experts, and rural areas remain unattractive for young specialists. The 2009 program "With a diploma to the village" seeking to attract young professionals to the countryside has had low success. The modernization of the agricultural education system would be impossible without an analysis of the external environment and various factors influencing the competitiveness of graduates. This study aims to analyze the motivation, aspirations and career expectations of students at agrarian universities and to develop recommendations for career planning and increasing the employment rates of graduates. General scientific and statistical methods were used, based on a student survey. According to the study results, domestic factors determine the choices students make in terms of university and specialty. Among Bachelor and Master students, there are still those who have not yet decided on an eventual profession. Over half of the undergraduate respondents have no clear career plans, and often unrealistic career expectations. The majority of the respondents are interested in urban jobs due to dissatisfaction with rural wage levels and living conditions. To achieve high levels of competitiveness and employment among agricultural university graduates, the following is recommended: improve students' motivation, facilitate the career plans of Bachelor students by introducing career planning courses, strengthen youth employment programs, include more agricultural specialties that are needed in rural areas, develop student entrepreneurship and practice-oriented training, improve rural living conditions, increase rural wages, and expand opportunities for career growth for young specialists in agriculture.
urn:nbn:de:gbv:3:2-81499
Keywords: I20; I21; I23; I28; 330; C; agricultural education; motivation; career expectations; Agrarausbildung; Motivation; Karriereerwartungen